The nitrogen and phosphorus influence on the fertility of soils from Campos Gerais, in the State of Paraná, Brazil - Ramos, Milton (Pesquisa Agropecuaria Brasileira, 2014)
The influence af nitrogen and phosphorus fertilization on the fertility of five soils from the Campos Gerais area in the State of Paraná, Brazil, was observed in greenhouse studies. These soils are derived from Ponta Grossa shale and Furnas sandstone, both are devonian sedimentary deposits. In their native state the soils derived from these parent materials have low levels of phosphorus, calcium and magnesium. This status may be modified after several years of cultivation, depending upon the level of management. Responses to phosphorus, as well as signifícant nitrogen x phosphorus interaction, were evident. There was a significant response to nitrogen on cultivated soils, even in the absence of phosphorus fertilization. Nitrogen response on the native soils was nil, unless phosphorus was applied. On the other hand, in the absence of nitrogen, only the native soils reacted significantly to phosphorus applications. Phosphorus residual was minimum, indicating that these soils have considerable capacity to fix phosphorus.